2015
DOI: 10.1039/c5ra03266k
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of potassium zinc hexacyanoferrate nanocubes and their potential application in photocatalytic degradation of organic dyes

Abstract: The novelty of work lies in the green synthesis of KZnHCF nanocubes using natural surfactant and impact on photocatalytic degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(23 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…It is further observed that synthetic CoONPs exhibit excellent degradation efficiency towards MX compared to TY. We have made a comparison of reactivity among the degradation efficiency of CoONPs photocatalysts towards different dyes and catalysts (Table 1) [40][41][42][43][44][45] . The present CoONPs shows an excellent efficiency compared to the other CoONPs.…”
Section: Photocatalytic Degradation Study Of Murexide and Titan Yellomentioning
confidence: 99%
See 1 more Smart Citation
“…It is further observed that synthetic CoONPs exhibit excellent degradation efficiency towards MX compared to TY. We have made a comparison of reactivity among the degradation efficiency of CoONPs photocatalysts towards different dyes and catalysts (Table 1) [40][41][42][43][44][45] . The present CoONPs shows an excellent efficiency compared to the other CoONPs.…”
Section: Photocatalytic Degradation Study Of Murexide and Titan Yellomentioning
confidence: 99%
“…Until date, few photocatalysts are known for the visible light induced degradation MX and TY [33,35,37] . For example, Adekunle et al [41] , studied the photocatalytic degradation of MX employing Co 3 O 4 nanoparticles in aqueous medium and found ~43.60% degradation efficiency (DE) under solar light irradiation for 40 mins. Recently, Hendekhale et al [44] , have reported the NPs.…”
Section: Photocatalytic Degradation Study Of Murexide and Titan Yellomentioning
confidence: 99%
“…72 Furthermore, the CoHCF possesses the light switchable magnetism, whereby a charge transfer induced spin transition between the Co II (high spin)-Fe III to Co III (low spin)-Fe II states alters magnetization. 70 Furthermore, Based on the different characteristic of transition metals, some efforts have been made to synthesize and investigate other MHCFs such, as ZnHCF, 73,74 MnHCF, 11,75 AgHCF 76 and YHCF. 70 Furthermore, Based on the different characteristic of transition metals, some efforts have been made to synthesize and investigate other MHCFs such, as ZnHCF, 73,74 MnHCF, 11,75 AgHCF 76 and YHCF.…”
Section: Other Mhcfsmentioning
confidence: 99%
“…Unlike the other Prussian blue analogues [22], zinc hexacyanoferrate (III) (ZnHCF) stands out as a unique exception in that it cannot be deposited easily on surfaces like glassy carbon (GC), Pt and Au, as procedures required for adhesion are too involved in nature [23][24][25][26]. In certain cases, ZnHCF films were obtained by electrochemical cycling of zinc electrodes in solutions containing ferricyanide [24], in which nascent Zn ions are produced during the anodic scan complex with ferricyanide in the solution.…”
Section: Introductionmentioning
confidence: 99%